Socio-Economic Analysis of Street Vendors after Relocationin Makassar City (Family Sociology Prospective Study) - Sam'un Mukramin; Fatimah Azis; Maemunah Maemunah; St. Haniah Haniah (Ilomata International Journal of Social Science, 2022)
This research contributes to knowledge and ideas in improving the welfare of street vendors after relocation due to the construction of a flyover. In addition, the government's alignment with socio-economic income in meeting the livelihoods and livelihoods of marginalized communities still has many limitations. Therefore, the type of research used is a qualitative research which aims to analyze, understand and describe the welfare of the street vendors after relocation. So this study shows that (i) PKL families on Jalan Andi Pangerang Pettarani cannot be said to be prosperous because they have not met the family welfare indicators, such as some families do not have savings have never been on vacation, which is one of the family indicators